Enhancing the Flow in Microchannel using Natural Polymeric Additives - Fiona Ling, Wang Ming; Abdulbari, Hayder A. (Informatics Publishing Limited, 2017)
This present study aims to study the feasibility of three natural polymeric drag reducing additives in enhancing the flow in microchannel. Five mucilage solution concentration (100 to 500 ppm) was prepared by adding deionized water which acted as transported liquid after extracting from okra, aloe vera and hibiscus leaves. The additives were then tested in custom made microchannel simulating human heart blood vessels. The flow performance of different concentration of additives was evaluated by recording the flow rate across the microchannel corresponding to the operating pressure (50 to 500 mbar). Increasing of the additives concentration increases the %FI indicating that drag reduction occurred. However, continuous increasing of the concentration has negative effect on drag reduction where this limit is known as critical concentration. The maximum drag reduction up to 63.48% is achieved using 300 ppm of hibiscus mucilage. This work introduces an approach for flow enhancement in semi-clogged blood streams using natural polymers that could contribute as an alternative treatment for cardiovascular diseases.